The Effectiveness of Teaching Biology Based on Electronic Mind Mapping Strategy on Achievement and Attitude Towards the Subject Among Tenth Basic Grade Students in Jordan - Sabra, Jihad Khader Radwan; Al - Jadri, Adnan Hussein (Journal of Educational and Psychological Sciences, 2019)
This study aimed to find the effectiveness of teaching biology based on electronic mind mapping strategy on achievement and attitude towards the subject among the tenth basic grade students in Jordan. To achieve the aim of the study, the researcher followed the semi-experimental design of the two equal groups.Two measurement tools were designed to achieve the aims of the study. The first one is the achievement test, which consists of 30 multiple-choice questions. The second one is a questionnaire to measure the attitudes towards Biology, Verifying their sincerity and consistency. The members of the study consist of (63) female students of Al- Khader Modern Schools. One of the two groups consists of (32) students were chosen randomly to be as an experimental group and to be taught using the electronic mind map while the other group - was controlled- consists of (31) students.The findings of the study showed;There is a statistical functional difference in the functional level (α = 0.05) in the tenth grade students' achievement in Biology and the attitudes toward the subject attributed to the effect of the teaching method in favor of the experimental group which was taught using the electronic mind maps in average of (24.59 out of 30) in the achievement where as (4.73 out of 5.00) towards the subject compared to the controlled group which was taught using the usual way in average of (21.55 out of 30) in the achievement out (4.07 out of 5.00) towards the subject. The differences were in favor of experimental group. The main recommendation of the study was to set up training programs for Biology teachers to let them know the importance of electronic mind maps in teaching Biology; the correct way of using it, and to clarify the role of both the teacher and the students according to this strategy. And to clarify.
Keywords: Effectiveness; Teaching Biology; Electronic Mind Maps Strategy; Tenth Elementary Students; Jordan